Dynamic properties of impact hammer operator and their influence on dynamics of lightweight structures. (7th July 2022) - Wei, Xiaojun; Zhang, Jingwei; Živanović, Stana; Liu, Jingliang; Russell, Justin; He, Xuhui
Highlights: Intra- and inter-subject statistics of a hammer operator's model are established. Procedure for removing effects of the operator on structure dynamics is presented. Bridges prone to interaction with a hammer operator are identified. Abstract: This paper considers the dynamics of a human in a crouching posture (assumed during manual impact hammer tests) and their influence on system dynamics. Intra-subject and inter-subject statistics for the dynamics of crouching humans are determined for three and nine test subjects, respectively. The average hammer operator's undamped natural frequency was 3.49 Hz with a damping ratio of 13.7%. Knowledge of the hammer operator dynamics is then utilised to identify the dynamic properties of the supporting structure in an unoccupied state. The results are verified on two fibre-reinforced polymer composite footbridges. Criteria for identifiability of the hammer operator-structure interaction are presented and used to identify bridge properties for which the hammer operator's influence on the structure can be compensated for.